A Consensus-Based Secondary Control Strategy for Hybrid Ac/Dc Microgrids with Experimental Validation - Espina-Gonzalez, E (Institute of Electrical and Electronics Engineers Inc., 2021)
Secondary control strategies in hybrid ac/dc microgrids have been conventionally designed independently for each side of the microgrid, neglecting the interaction between the ac and dc sides due to the power transferred through the interlinking converter. This has a negative effect on the power sharing and dynamic response of the system. In this article, a novel distributed secondary control strategy for hybrid ac/dc-microgrids is presented which coordinates the control actions of the ac and dc sides. The proposed control scheme simultaneously regulates ac-voltage magnitude and frequency, as well as the dc-voltage magnitude, by including the interlinking converters in the control strategy via a distributed consensus approach. This improves the power-sharing accuracy and secondary control restoration of the variables in both ac and dc sides of the microgrid. Moreover, the proposed methodology avoids the circulating currents which are typically produced in systems with multiple interlinking converters. Several simulation and experimental tests, such as load impacts and plug-and-play capability, are presented to validate the performance of the proposed control strategy using a 24-kW hybrid ac/dc-microgrid laboratory prototype. © 1986-2012 IEEE.